PENGARUH INTANGIBLE ASSET TERHADAP KINERJA KEUANGAN DENGAN KEUNGGULAN BERSAING SEBAGAI MEDIASI - Ika Purwanti; Mu’ah . (Universitas Mercu Buana, 2019)
This study aims to examine and analyze the effect of intangible asset on financial performance with competitive advantage as a mediation at Tenun Ikat SMEs Lamongan. The research development is done by by studying and analyzing both the direct effect of intangible asset on financial performance, and indirect effect through competitive advantage. The research sample is 35 business units selected using saturated sampling method, that is all the members of the population sampled. Data is analyzed by Partial Least Square (PLS) with SmartPLS 3.0 software. The results show that intangible asset has significant effect on competitive advantage, but has no significant effect on financial performance. Competitive advantage is related to financial performance. The mediation test indicates that competitive advantage gives the role as a complete mediation on the effect of intangible asset on financial performance. This research implies that in order to enhance SME’s financial performance, the manager should ensure that the firm has a competitive advantage. A well managed intangible asset will lead SMEs to win the completion and at the end it will enhance SME’s financial performance.